2009
DOI: 10.1177/0363546508331134
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of Medial Collateral Ligament Reconstructions Using Computer-Assisted Navigation

Abstract: Although the medial collateral ligament often heals without surgical intervention, surgical reconstruction is occasionally necessary in grade III medial collateral ligament and combined ligamentous injuries to the knee. Double-bundle reconstruction of the medial collateral ligament better resists valgus forces across the knee and may allow for better surgical outcome after medial collateral ligament reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 37 publications
1
50
0
Order By: Relevance
“…These included donor site morbidity and nonanatomic insertion site of the MCL graft on the tibia (ie, too anterior) when preserving the insertion of a semitendinosus autograft [2,5,17,20], need for long incisions across the medial side of the knee, and relative technical complexity when using double-bundle constructs [4,9,11,17,30]. Harvesting a dynamic medial stabilizer that applies adduction moment during gait (ie, semitendinosus) in a knee with an already medial instability may pose another limitation in our opinion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These included donor site morbidity and nonanatomic insertion site of the MCL graft on the tibia (ie, too anterior) when preserving the insertion of a semitendinosus autograft [2,5,17,20], need for long incisions across the medial side of the knee, and relative technical complexity when using double-bundle constructs [4,9,11,17,30]. Harvesting a dynamic medial stabilizer that applies adduction moment during gait (ie, semitendinosus) in a knee with an already medial instability may pose another limitation in our opinion.…”
Section: Discussionmentioning
confidence: 99%
“…However, when MCL injuries fail to heal, reconstruction may be advised to correct chronic instability or to prevent valgus overload on a reconstructed cruciate ligament [19,26]. Several techniques have been described to reconstruct the MCL including semitendinosus autograft with preservation of the tibial insertion [2,5,17,20], allograft tissues [4,9], and double-bundle reconstructions [4,9,11,17,30]. However, some of these investigators who used a long incision across the medial aspect of the knee reported up to 20°loss of knee flexion or extension in 20% of their operations [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zaffagnini has used a CAS system to investigate static and dynamic laxity parameters following double-bundle ACL reconstruction [25,48,49]. These data could also be used to assess the effect of different surgical techniques on knee stability following other ligament reconstruction, including posterior cruciate ligament [50], medial collateral ligament [51], and posterolateral corner reconstructions [52]. CAS data have also been used to assess the effect of the different ACL bundles on knee kinematics in double-bundle reconstruction, but so far results are inconsistent [25,[53][54][55].…”
Section: Research Applications In Knee Ligament Surgerymentioning
confidence: 99%
“…Most biomechanical studies on knee joints and surrounding tissue behavior are based on experiments or simplified joint models. 27,28 However, it is difficult to make direct comparisons between the reported experimental or modeling-based studies, which differ in kinematic modeling methods, test structure, mechanical properties, and bone surface geometry. Experimental kinematic analysis of joints is usually based on anatomical landmarks that limit reproducibility.…”
mentioning
confidence: 99%